Implementation of Apem Cake Media as Mathematics Teaching Materials in Elementary School - Anggi Tri Yuanda Putri; Feny Rita Fiantika; Susi Hermin Rusminati (Formosa Journal of Sustainable Research, 2023)
This study aims to implement culture-based learning on apem cake as a mathematics teaching material at SDN Tenggilis Mejoyo I Surabaya which is applied to class IV-B. This research uses a qualitative method with an ethnographic approach where this approach is used to find out the unit of weight in mathematical concepts contained in the ingredients of apem cake. Based on the results of this study, it shows that the implementasi of apem cake media as a mathematics teaching material in elementary schools is going well. Judging from the results of teacher observation and learner observation, it is in accordance with the material achievement indicators. This can also be seen in the results of the written test of students, out of 25 students in class IV-B there are 17 students who are in the high category who are able to exceed the achievement indicators of the material measurement of units of weight on apem cakes. The results of the students' response questionnaire are in line with the results of observations and written test results. Based on the results of teacher observations, student observations, written test results and student response questionnaires, it can be concluded that the implementation of apem cake media as a mathematics teaching material for measuring units of weight is an innovation for Tenggilis Mejoyo I Surabaya Elementary School